2013
DOI: 10.1111/jsm.12266
|View full text |Cite
|
Sign up to set email alerts
|

Serum PSA as a Predictor of Testosterone Deficiency

Abstract: Introduction The relationship between serum prostate-specific antigen (PSA) and testosterone (T) levels is still controversial. According to the “saturation hypothesis,” a significant relationship is apparent only in the low T range. Aim To verify whether, in a large sample of male subjects seeking medical care for sexual dysfunction (SD), PSA might represent a reliable marker of T levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 52 publications
9
66
2
1
Order By: Relevance
“…More recently, the 'saturation model' emerged [Morgentaler and Traish, 2009], establishing that prostate tissue, benign or malignant, is only sensitive to serum levels of testosterone below a certain threshold, above which prostate tissue behaves irrespective of androgen levels. Other data have confirmed these findings and propose a threshold level of approximately 8.6 mmol/l [Rastrelli et al 2013]. Several studies also support the use of testosterone in men 'at risk' for prostate cancer without increasing their baseline odds of prostate cancer development [Roddam et al 2008;Muller et al 2012;Cui et al 2014].…”
Section: Controversies and Risksupporting
confidence: 61%
“…More recently, the 'saturation model' emerged [Morgentaler and Traish, 2009], establishing that prostate tissue, benign or malignant, is only sensitive to serum levels of testosterone below a certain threshold, above which prostate tissue behaves irrespective of androgen levels. Other data have confirmed these findings and propose a threshold level of approximately 8.6 mmol/l [Rastrelli et al 2013]. Several studies also support the use of testosterone in men 'at risk' for prostate cancer without increasing their baseline odds of prostate cancer development [Roddam et al 2008;Muller et al 2012;Cui et al 2014].…”
Section: Controversies and Risksupporting
confidence: 61%
“…PSA is a serine protease produced from the prostate gland under androgenic control, and has been postulated as an effective predictor of prostate volume [49], a marker of testestoterone concentrations, and a valuable tool in confirming hypogonadism [50]. The present study revealed that BDL rats had smaller prostate glands and lower serum PSA levels in comparison to sham ones.…”
Section: Discussionmentioning
confidence: 53%
“…More recently, prostate-specific antigen (PSA) has been proposed as a tissue marker of testosterone deficiency: in a large cohort of O3000 men, a PSA of !0.65 mg/l predicted a total testosterone of !8 nmol/l with modest sensitivity (65%) and specificity (56%). A low PSA was associated with delayed puberty, lower testicular volume and interestingly, with the presence of the metabolic syndrome (hazard ratio 1.5 (1.2-1.8), P!0.001) and type 2 diabetes (hazard ratio 2.0 (1.7-2.5), P!0.001) (Rastrelli et al 2013). In a cohort of 138 men with type 2 diabetes, free testosterone levels were inversely associated with bone density at some but not all sites (Dhindsa et al 2007).…”
Section: End Organ Deficits Of Androgen Deficiencymentioning
confidence: 99%